Management of myocardial infarction with non-obstructive coronary arteries (MINOCA) in Germany: a single-center study on hospital resources and healthcare economics - Haertel, Franz; Montag, Carolin; Kraeplin, Thomas; Lauer, Bernward; Memisevic, Nedim; Moebius-Winkler, Sven; Schulze, P. Christian; Otto, Sylvia (Frontiers in Public Health, 2024)
Patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) present with ≤ 50% stenosis on angiography despite acute coronary syndrome symptoms and biomarker elevation. We investigated MINOCA's hospital workflow, economic impact, and outcomes vs. myocardial infarction with obstructive coronary artery disease (MICAD) in a single-center study. Retrospectively analyzing 660 acute coronary syndrome cases (2017-2018), 118 were MINOCA and 542 MICAD. MICAD had higher in-hospital (11% vs. 0%; p<0.001) and 30-day mortality (17.3% vs. 4.2%; p<0.001). Although MINOCA had shorter hospital stays (9.5 ± 8.7 vs. 12.3 ± 10.5 days, p<0.01) and less high care monitoring (2.4 ± 2.1 vs. 4.7 ± 3.3 days, p<0.01), they still utilized significant resources, attributing a total sum of nearly 300 days in high - care monitoring days over 12 months. Despite lower treatment costs, MINOCA did not yield a profit, with 40% of costs attributed to high care monitoring. Given relatively low mortality and resource scarcity, MINOCA warrants attention for care refinement and resource allocation.